Physics Virtual Experiment sebagai Solusi Praktikum Fisika pada Pembelajaran Daring Kelas XI Tingkat SMA pada Materi Elastisitas - Putri, Syafira Setya; U.S, Supardi (UNIVERSITAS INDRAPRASTA PGRI, 2024)
Online learning due to the COVID-19 pandemic has hindered the implementation of physics practicums that are usually conducted face-to-face in the laboratory. This study aims to examine the effectiveness of Physics Virtual Experiment (PVE) based on the Crocodile Physics application as a solution for online physics practicums on the topic of elasticity for 11th-grade high school students. An experimental method with the ANCOVA approach was used in this study, involving two groups of students: the experimental group that used the Physics Virtual Experiment and the control group that followed conventional learning methods. The results of the study showed a significant improvement in the understanding of elasticity concepts in the experimental group. Thus, the Physics Virtual Experiment can be an effective solution for physics practicums during online learning.